Using developmental evaluation as a system of organizational learning: An example from San Francisco. (December 2017) - Shea, Jennifer; Taylor, Tory
Highlights: Developmental evaluation can provide a system of tools, methods, and principles to catalyze organizational learning. The pilot framework helped address three challenges to engaging organizational learning in emergent programs. Presents a new framework to help evaluators focus inquiry on factors related to organizational learning and complexity. The Evaluation-led Learning framework includes two pre-project assessments meant to ensure productive organizational learning. Abstract: In the last 20 years, developmental evaluation has emerged as a promising approach to support organizational learning in emergent social programs. Through a continuous system of inquiry, reflection, and application of knowledge, developmental evaluation serves as a system of tools, methods, and guiding principles intended to support constructive organizational learning. However, missing from the developmental evaluation literature is a nuanced framework to guide evaluators in how to elevate the organizational practices and concepts most relevant for emergent programs. In this article, we describe and reflect on work we did to develop, pilot, and refine an integrated pilot framework. Drawing on established developmental evaluation inquiry frameworks and incorporating lessons learned from applying the pilot framework, we put forward the Evaluation-led Learning framework to help fill that gap and encourage others to implement and refine it. We posit that without explicitly incorporating the assessments at the foundation of the Evaluation-led Learning framework, developmental evaluation's ability to affect organizational learning in productive ways will likely be haphazard and limited.